Inequality in the Distribution of Household Expenditure in Cameroon - Samuel Fambon (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
In the literature, it is generally accepted that consumption is a more appropriate welfare measure than household income or salaries. This paper aims to investigate the evolution of expenditure inequality in Cameroon over the 1984-1996 period, with the help of Lorenz Curves, the Gini coefficient, and two entropy measures of inequality. Total expenditure inequality is decomposed into the within-groups and between-groups components using Theil's decomposition techniques and household expenditure data derived from the 1984 and 1996 National household surveys (i.e. the 1983/1984 Household Consumption Budget (EBC) survey, and the 1996 Cameroonian Household Survey (ECAM1)). Decompositions are carried out according to the residence area (rural, semi-urban, and urban), stratum, age, educational level and the gender of the household head. Policy implications are discussed.
Keywords: 330; Inequality; Expenditure; Decomposition; Household Surveys; Cameroon